Assessing the Role of Renewable Energy Policies in Achieving India's Sustainable Development Goals by 2047 - Monika, Monika; Katoch, Rupinder (Journal of Neonatal Surgery, 2025)
India's journey towards sustainable development is mostly depends on its renewable energy and renewable energy policies, which are central to achieving the India’s Sustainable Development Goals (SDGs). This research paper provides a comprehensive analysis of the impact of India's renewable energy initiatives on the India’s progress towards SDGs goals. It also evaluates the effectiveness of current policies, and identifies existing challenges, and explores the potential for future opportunities of expansion in the renewable energy sector. The study emphasizes the need for policy refinement, technological innovation, and strategic interventions to overcome barriers and ensure that India not only meets but exceeds its sustainability targets by 2047—the centenary of its independence. This timeline is crucial as it represents a significant milestone in India's commitment to becoming a global leader in sustainable energy and development.